Identification and Development of Inflammatory Response–Related Genes Signature Associated With Prognosis Evaluation and Immune Status of Bladder Cancer - Zheng, Haoxiang; Luo, Weihan; Li, Yuqing; Peng, Guoyu; Zhou, Dewang; Tang, Dongdong; Cheng, Jiwen; Wu, Song (Frontiers in Cell and Developmental Biology, 2022)
Background: Bladder urothelial carcinoma (BLCA) is one of the most common malignant tumors with high morbidity and recurrence rate. The study aims to establish a prediction model to elaborate the relation between inflammatory response and prognosis of BLCA, thus to evaluate the potential prognostic value of inflammatory response-related genes (IRGs) in therapeutic choices. Methods: The study utilized the gene expression profiles from TCGA and GEO (GSE32894) datasets. Differentially expressed IRGs between normal and tumor tissues were identified and ten of them were correlated with overall survival (OS) (P < 0.05). Then, the LASSO-Cox regression analysis was applied to optimize the signature. RNA-seq data of BLCA patients from GSE32894 were applied as a validation set. Cox regression analyses of the 7-gene signature were performed to examine the efficiency of signature in predicting prognosis. Receiver operating characteristic (ROC) curve analysis was applied to measure the predictive performance of the risk score for OS. Analysis of independent prognostic factors, downstream functional enrichment, drug sensitivity and immune features were included in this study. Results: The IRGs signature (LDLR, ROS1, MMP14, TNFAIP6, MYC, PTGER4, RIPK2) was used to divide patients into high- and low-risk groups. Cox regression analyses revealed that the risk score was an independent predictive factor. Functional enrichment analysis revealed that genes were enriched in prognosis-related molecular functions and immune-related biological processes. Drug sensitivity and tumor microenvironment correlation analysis indicated the signature was related to immunotherapy effect. Conclusion: The study defined a new prognostic signature consisting of seven IRGs, which could effectively predict the prognosis of BLCA patients, and reveal relationship of immune features in BLCA with different risk scores. The study also provided a possible indicator for targeted therapy.